Potential for improving the efficiency of terrigenous oil deposits waterflooding with the use of low salinity technology at fields of the Tatarstan Republic - Z. R. Saptarova; A. A. Mamonov; S. A. Usmanov; A. A. Lutfullin; V. A. Sudakov; M. S. Shipaeva; A. A. Shakirov (Georesursy, 2024)
This article is devoted to the review of one of the currently relevant methods of enhanced oil recovery – low-salinity waterflooding (LSW) – on the example of terrigenous Tulian, Bobrikovian and Devonian reservoirs of the Tatarstan Republic fields.The first part of review contains information about the key processes underlying this method, such as swelling and migration of clay particles and wettability alteration, as well as the mechanisms that explain these processes, which include cation exchange, multicomponent ion exchange, electric double layer expansion, etc. Their understanding, in turn, contributes to the identification of the main factors, the presence or absence of which at the field allows us to give a preliminary assessment of LSW application. There are main factors: the presence of clay particles, a significant content of Ca2+ and Mg2+ ions, as well as multivalent ions in formation water, low formation permeability, reduced oil viscosity, an increased content of acidic and especially basic components in oil and, as a result, a hydrophobic type of initial rock wettability.Then, examples of using the method in other fields are given and the results of laboratory studies, including the measurement of the contact angle, core flooding experiments, are briefly highlighted.A preliminary screening is carried out on the basis of geological and field data from several fields of Tatarstan Republic, candidate fields are identified and a preliminary conclusion about LSW application in this region is made. The positive factors for the reservoirs under consideration, identified at the preliminary screening stage, include low formation temperature, high salinity of formation water with a significant content of divalent cations and the potential to shift the pH level from the current slightly acidic level towards increased alkalinity, and an increased content of polar oil components. In addition, the reservoirs of the Tulian and Bobrikovian horizons are characterized by the presence of clay particles, and the Devonian reservoir are characterized by a reduced oil viscosity coupled with an increased oil base number.